Glucocorticoids modulate human brown adipose tissue thermogenesis in vivo - Scotney, Hannah; Symonds, Michael E.; Law, James; Budge, Helen; Sharkey, Don; Manolopoulos, Konstantinos N. (WB Saunders, 2017)
Introduction: Brown adipose tissue (BAT) is a thermogenic organ with substantial metabolic capacity and has important roles in the maintenance of body weight and metabolism. Regulation of BAT is primarily mediated through the ß-adrenoceptor (ß-AR) pathway. The in vivo endocrine regulation of this pathway in humans is unkown. The objective of our study was to assess the in vivo BAT temperature responses to acute glucocorticoid administration. Methods: We studied 8 healthy male volunteers, not pre-selected for BAT presence or activity and without prior BAT cold-activation, on two occasions, following an infusion with hydrocortisone (0.2 mg.kg-1.min-1 for 14 hours) and saline, respectively. Infusions were given in a randomized double-blind order. They underwent assessment of supraclavicular BAT temperature using infrared thermography following a mixed meal, and during ß-AR stimulation with isoprenaline (25 ng.kg fat-free mass-1.min-1 for 60 min) in the fasting state. Results: During hydrocortisone infusion, BAT temperature increased both under fasting basal conditions and during ß-AR stimulation. We observed a BAT temperature threshold, which was not exceeded despite maximal ß-AR activation. We conclude that BAT thermogenesis is present in humans under near-normal conditions. Glucocorticoids modulate BAT function, representing important physiological endocrine regulation of body temperature at times of acute stress.